Structural-parametric synthesis of hydro-mechanical drive of hoisting and lowering mechanism of package-forming machines - Gavva, Oleksandr M.; Kryvoplias-Volodina, Liudmyla; Yakymchuk, Nikolai (My University, 2017)
The analysis of the operation of the lifting and lowering mechanisms of the package forming machines and the synthesis of the structure was performed hydromechanical drive. Theoretically the mode of operation of a hydromechanical drive with a hydrogas accumulator was investigated. The objective function of energy consumption minimization is formulated during step filling of the battery. Experimentally confirmed, that the compression of the gas in the accumulator of the lifting-lowering mechanism is described by an adiabat. Defined hypothetical polytropy index. The parameters of the hydraulic drive are determined, which will provide a minimum of the objective function of cost minimization energy. Виконано аналіз роботи піднімально-опускних механізмів пакетоформуючих машин та синтез структури гідромеханічного привода. Теоретично досліджено режим роботи гідромеханічного привода із гідрогазовим акумулятором. Сформульована цільова функція мінімізації витрат енергії при кроковому заповненні акумулятора. Експериментально підтверджено, що стискання газу в акумуляторі піднімально-опускного механізму описується адіабатою. Визначено гіпотетичний показник політропи. Визначено параметри гідропривода, що забезпечить мінімум цільової функції мінімізації витрат енергії
Keywords: lifting and lowering mechanism; hydromechanical drive; battery; packet maker; potential energy; кафедра мехатроніки та пакувальної техніки; піднімально-опускний механізм; гідромеханічний привод; акумулятор; пакетоформуюча; потенціальна енергія